Rooting of healthy and CVC-affected 'Valência' sweet orange stem cuttings, through the use of plant regulators - Habermann, Gustavo [UNESP]; Alvarez, Rita de Cássia Félix [UNESP]; Modesto, Júnior Cesar [UNESP]; Fortes, Andréa Maria Teixeira [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Brazilian Archives of Biology and Technology, 2006)
Clorose variegada dos citros (CVC) é uma doença causada por Xylella fastidiosa, podendo determinar oclusão do xilema e desbalanço hormonal, o que por fim está relacionado ao processo de iniciação radicial em estacas. Usando diferentes concentrações de fitorreguladores, como auxinas (ácido 3-indol butírico) e inibidores da biossíntese de ácido giberélico (paclobutrazol), que são promotores do enraizamento de estacas, verificou-se a capacidade fisiológica de enraizamento de estacas sadias e com CVC, a fim de investigar a importância do desbalanço hormonal e oclusão do xilema em plantas doentes. As porcentagens de estacas mortas, vivas, enraizadas e com calo e o número médio de raízes por estaca não mostraram diferenças estatísticas em resposta às diferentes concentrações dos reguladores vegetais sintéticos. Houve diferenças apenas entre estacas sadias e doentes. Isto aponta a importância da oclusão do xilema e distúrbios difusivos em plantas doentes, em relação à capacidade de iniciação radicial e à translocação hormonal no tecido vegetal.

Citrus variegated chlorosis (CVC) is a disease caused by Xylella fastidiosa. Using different concentrations of plant regulators, such as auxins (indole-3-butyric acid) and gibberellic acid biosynthesis-inhibitor (paclobutrazol), physiological rooting capacity of healthy and CVC-affected stem cuttings were evaluated in order to investigate the importance of plant hormone imbalance and xylem occlusion in plants with CVC. The percentages of dead, alive and rooted cuttings, cuttings with callus and mean number of roots per cuttings did not show statistical differences in response to the distinct concentrations of synthetic plant regulators. There were differences only between healthy and CVC-affected cuttings. This showed the importance of xylem occlusion and diffusive disturbances in diseased plants, in relation to root initiation capacity and hormonal translocation in the plant tissue.
Keywords: IBA; Paclobutrazol; Xylella fastidiosa; root initiation; Citrus sinensis